The effects of acupressure and back massage on reducing mother’s pain during fisrt stage of labor at Pratama Hadijah Maternity Clinic - Nasution, Annisa Namirah; Sitorus, Nopita Yanti; Lubis, Desi Handayani; Fauziah, Yaumil; R, Maimunah; Nasution, Yulia Fatma (Science Midwifery, 2025)
This study aims to analyze the effect of acupressure and back massage on reducing mother’s pain during first stage of labor at Pratama Hadijah Maternity Clinic 2024. It was a quantitative research using experimental research design with non-equivalent control group design. The samples were 40 mothers who experiencing first stage of labor. They were selected by using accidental sampling. The data were collected by using NRS (Numeric Rating Scale) observation sheet. The data were analyzed by using unvaried and bivariate data analysis with Wilcoxon Test. The findings showed the level of pain before applying acupressure therapy majority about 18 respondents (90%) experienced moderate pain and after applying acupressure therapy majority 13 respondents (65%) experienced mild pain. Whereas about 16 respondents (80%) experienced moderate pain before applying acupressure therapy and about 12 respondents (60%) experienced moderate pain after applying back massage. There is an influence of acupressure therapy (p=0,001) and back massage (p=0,000<) on the reducing the level of mothers ‘pain during the first stage of labor. It is concluded that there is an influence of acupressure therapy and back massage on reducing mother’s pain during the first labor at Pratama Hadijah Maternity Clinic 2024. It is suggested to the clinic to apply acupressure therapy which is proven more effective and can be taught to pregnant woman, maternity, and family to reduce mothers ‘pain during first stage of labor.